Electrochemical Degradation Of Reactive Red 4 Using Graphite/Chitosan-Poly(Vinyl Chloride) Composite Electrodes - Mohd Halim, Nadhra Hidayah (2021)
In this study, graphite/chitosan-poly(vinyl chloride) (C/Chi-PVC) composite electrode was used as anode to investigate the degradation of Reactive Red 4 (RR4) in the presence of graphite rod and sodium chloride (NaCl) respectively as cathode and supporting electrolytes.